Oral health-related quality of life of elderly people and associated sociodemographic factors - Alberto Miranda-Medina; Julio Alcocer-Nuñez (Universidad de Concepción., 2021)
Introduction: Oral health plays a key role in people's quality of life. This is especially relevant in vulnerable groups such as the elderly. Objective: To determine how the sociodemographic characteristics of the elderly in a city of Arequipa (Peru) are associated with Oral Health-related Quality of Life (OHRQoL). Material and Methods: A descriptive, prospective, cross-sectional study consisting of 240 older adults, was carried out between October and December of 2019. Sociodemographic characteristics were assessed by means of a questionnaire, while oral health-related quality of life was evaluated using the Oral Health Impact Profile (OHIP-14). A descriptive analysis was performed to study the distribution of oral health-related quality of life and sociodemographic characteristics. An inferential analysis was performed to determine the association between the study variables. Results: Most of the older adults were aged between 60-65 years (32.1%). Female participants were the most prevalent group accounting for 60.8%; 42.5% had completed secondary education; 45.4% were married; and 46.7% were covered by a Comprehensive Health Insurance system (SIS, for its acronym in Spanish); 42.9% lived in a extended-family household; and more than half of the respondents reported an income below the minimum living wage (64.2%). Most of the older adults perceived that their oral health did not have a negative impact on their quality of life, with excellent (45.4%) and moderate (34.6%) assessments of their oral health-related quality of life. The most affected dimensions were psychological discomfort (84.2%) and functional limitation (72.1%). Age, educational level, marital status, type of insurance, and level of income had a statistically significant relationship with oral health-related quality of life (p<0.05). Conclusion: Most of the sociodemographic characteristics analyzed are indeed related to the perception of older adults in this study as to how oral health impacted their quality of life.